Inhibitory Effect of Multimodal Nanoassemblies against Glycative and Oxidative Stress in Cancer and Glycation Animal Models. (10th April 2021) - Khan, Hamda; Waseem, Mohd; Faisal, Mohammad; Alatar, Abdulrahman A.; Qahtan, Ahmed A.; Ahmad, Saheem
Abstract : In recent years, there has been a progress in the study of glycation reaction which is one the possible reason for multiple metabolic disorders. Glycation is a nonenzymatic reaction between nucleic acids, lipids, and proteins resulting into the formation of early glycation products that may further lead to the accumulation of advanced glycation end products (AGEs). The precipitation of AGEs in various cells, tissues, and organs is one of the factors for the initiation and progression of various metabolic derangements including the cancer. The AGE interaction with its receptor "RAGE" activates the inflammatory pathway; yet, the downregulation of RAGE and its role in these pathways are not clear. We explore the effect of anticancer novel nanoassemblies on AGEs to determine its role in the regulation of the expression of RAGE, NFƙB, TNF- α, and IFN- γ . This paper is based on the in vivo and in vitro study in glycation and lung cancer model systems. Upon the treatment of nanoassemblies in both the model systems, we observed a protective effect of nanoassemblies over the inhibition of glycative and oxidative stress via mRNA expression analysis. The mRNA expression results corroborated with the reactive oxygen species (ROS), carboxy-methyl-lysine (CML), and fluorescence studies. In this study, we found that the presence of common factors for glycation and lung cancer is oxidative and glycative stress. This oxidation and glycation might be responsible for the initiation of inflammation which may further lead to uncontrolled growth of cells leading to cancer. This can be a strong association between lung cancer and glycation reaction. The intervention of the anticancer and antiglycation effects of multimodal nanoassemblies throughout the study promises a new pathway for cancer research.